1993
DOI: 10.1002/bit.260411111
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic waste‐activated sludge digestion–a bioconversion mechanism and kinetic model

Abstract: The anaerobic bioconversion of raw and mechanically lysed waste-activated sludge was kinetically investigated. The hydrolysis of the biopolymers, such as protein, which leaked out from the biological sludge with ultrasonic lysis, was a first-order reaction in anaerobic digestion and the rate constant was much higher that the decay rate constant of the raw waste activated sludge. An anaerobic digestion model that is capable of evaluating the effect of the mechanical sludge lysis on digestive performance was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 11 publications
1
48
0
3
Order By: Relevance
“…Typically a first order function is used to model anaerobic sludge hydrolysis (East man and Ferguson, 1981;Lilley et al, 1990;Eliosov and Argaman, 1995;Shimizu et al, 1993), although other expression such as the Contois model have been used to describe hydrolysis in aerobic systems (Dold et al, 1980). The first order approach has been shown to fit experimental data extremely well and it is doubtful if a more complicated expression is necessary.…”
Section: Kinetics Of Hydrolysismentioning
confidence: 99%
“…Typically a first order function is used to model anaerobic sludge hydrolysis (East man and Ferguson, 1981;Lilley et al, 1990;Eliosov and Argaman, 1995;Shimizu et al, 1993), although other expression such as the Contois model have been used to describe hydrolysis in aerobic systems (Dold et al, 1980). The first order approach has been shown to fit experimental data extremely well and it is doubtful if a more complicated expression is necessary.…”
Section: Kinetics Of Hydrolysismentioning
confidence: 99%
“…Hydrolysis being the rate limiting step for the biological degradation of WAS (Li and Noike, 1992;Shimizu et al, 1993), the introduction of a thermal hydrolysis pretreatment has proven to be a very interesting option (Kepp et al, 1999;Bougrier et al, 2008;Carrère et al, 2010), currently implemented full-scale (mainly Cambi® and Biothelys®).…”
Section: Introductionmentioning
confidence: 99%
“…However, waste activated sludge (WAS) is known to be more difficult to digest than primary sludge (PS) [2]. It has been reported that hydrolysis is the rate-limiting step in anaerobic digestion [3,4]. Extracellular polymeric substances (EPS) and microbial cells are recalcitrant to direct hydrolysis, and therefore, the pretreatment of sludge is required to rupture the cell walls, to facilitate the release of intracellular material into the aqueous phase and accelerate the low rate of biodegradation, and to enhance anaerobic digestion [5].…”
Section: Introductionmentioning
confidence: 99%